The Use of Kuwe Fish Seeds (Caranx sp) Catch Result on the Increase of Fishing Business Production with Fixed Net Cage System in Kendari City - Sardianti Sardianti; Muhammad Aswar Limi; Samsul Alam Fyka (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
This research will examine the usage of kuwe fish (Caranx sp) seeds that fishers catch in the wild. From September 2021 to March 2022, 36 fishermen who were kuwe fish cultivators participated in this study in Kendari City. The data utilized in this research were analyzed using multiple linear regression. The study's findings primarily indicated that the output of the fisheries industry using the fixed net cage method in Nambo District, Kendari City, was significantly impacted by the usage of variable Kuwe fish seeds obtained by fishers in the wild. The fixed net cage method in Kendari City allows fishers to continue using the kuwe fish they catch to boost fishing company productivity.